Identification of Anti-Severe Acute Respiratory Syndrome-Related Coronavirus 2 (SARS-CoV-2) Oxysterol Derivatives In Vitro - Ohashi, Hirofumi; Wang, Feng; Stappenbeck, Frank; Tsuchimoto, Kana; Kobayashi, Chisa; Saso, Wakana; Kataoka, Michiyo; Yamasaki, Masako; Kuramochi, Kouji; Muramatsu, Masamichi; Suzuki, Tadaki; Sureau, Camille; et al. (International journal of molecular sciences, 2021)
The development of effective antiviral drugs targeting the severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) is urgently needed to combat the coronavirus disease 2019 (COVID-19). We have previously studied the use of semi-synthetic derivatives of oxysterols, oxidized derivatives of cholesterol as drug candidates for the inhibition of cancer, fibrosis, and bone regeneration. In this study, we screened a panel of naturally occurring and semi-synthetic oxysterols for anti-SARS-CoV-2 activity using a cell culture infection assay. We show that the natural oxysterols, 7-ketocholesterol, 22(R)-hydroxycholesterol, 24(S)-hydroxycholesterol, and 27-hydroxycholesterol, substantially inhibited SARS-CoV-2 propagation in cultured cells. Among semi-synthetic oxysterols, Oxy210 and Oxy232 displayed more robust anti-SARS-CoV-2 activities, reducing viral replication more than 90% at 10 μM and 99% at 15 μM, respectively. When orally administered in mice, peak plasma concentrations of Oxy210 fell into a therapeutically relevant range (19 μM), based on the dose-dependent curve for antiviral activity in our cell-based assay. Mechanistic studies suggest that Oxy210 reduced replication of SARS-CoV-2 by disrupting the formation of double-membrane vesicles (DMVs); intracellular membrane compartments associated with viral replication. Our study warrants further evaluation of Oxy210 and Oxy232 as a safe and reliable oral medication, which could help protect vulnerable populations with increased risk of developing COVID-19.